La poesía de Tania Pleitez Vela: memoria y rememoración - Jossa, Emanuela (2018)
The present paper analyses two works by Salvadorean poetess Tania Pleitez Vela, Nostalgia del presente and Preguerra, published in 2014 and 2017 respectively. The paper will investigate these two collections of poems and their distinctive poetics of memory by emphasizing the author’s trajectory from the impossibility of accepting the past and naming grief, to the awareness of belonging. In this light, the paper will suggest that while Nostalgia del presente outlines the painful process of remembrance through a vulnerable and restless poetic self, in Preguerra the narrative of memory is conveyed by a more measured and introspective voice.